Effects of maternal diabetes on male offspring: high cell proliferation and increased activity of MMP-2 in the ventral prostate - Damasceno, A. A.; Carvalho, C. P.; Santos, E. M. B.; Botelho, F. V.; Araujo, F. A.; Deconte, S. R.; Tomiosso, T. C.; Balbi, A. P. C.; Zanon, R. G.; Taboga, S. R. [UNESP]; Goes, R. M. [UNESP]; Ribeiro, D. L. (Springer, 2014)
This study presents a comprehensive view of the histological and functional status of the prostate of adult rat offspring of mothers subjected to gestational diabetes induced by alloxan. The ventral prostate of male adult offspring of diabetic (DP) or normal (CP) mothers was evaluated for collagen fibres, cell death, fibroblasts, smooth muscle cells, cell proliferation, matrix metalloproteinases (MMPs), androgen receptors (AR), transforming growth factor beta 1 (TGF beta-1), catalase and total antioxidant activity. The prostates of DP animals were lower in weight than those of the CP group. The DP group also exhibited hyperglycaemia and hypotestosteronemia, higher cell proliferation and AR expression, a reduction in alpha-actin (possibly interfering with the reproductive function of the prostate), and enhanced activity of MMP-2, although the absolute content of MMP-2 was lower in this group. These findings were associated with increased TGF beta-1 and decreased collagen distribution. The prostates of DP rats additionally exhibited reductions in catalase and total antioxidant activity. Thus, rats developing in a diabetic intrauterine environment have glycaemic and hormonal changes that impact on the structure and physiology of the prostate in adulthood. The increased AR expression possibly leads to elevated cell proliferation. Stromal remodelling was characterized by enhanced activity of MMP-2 and collagen degradation, even with increased TGF beta-1 activation. These changes associated with increased oxidative stress might interfere with tissue architecture and glandular homeostasis.
Keywords: Maternal diabetes; Prostate; Cell proliferation; Metalloproteinase; Androgen receptor; Rat (Wistar)